Hubungan Kematangan Emosi Dengan Pemaafan (Forgiveness) Pada Remaja Akhir Yang Pernah Mengalami Putus Cinta Di SMAN 1 Marisa - Mutia Hamid; Lenny Syamsuddin; Sitti Rojiyah N.I Puhi (CV. Ulil Albab Corp, 2026)
This study aims to examine the relationship between emotional maturity and forgiveness among late adolescents who have experienced a romantic breakup at SMAN 1 Marisa. The background of this research is based on the phenomenon that many adolescents face difficulties in managing emotions and forgiving after the failure of romantic relationships. This study employed a quantitative approach with a correlational method. The sample consisted of 78 grade XI students categorized as late adolescents who had experienced a breakup. The sample was determined using the Isaac and Michael table with a purposive sampling technique. The research instruments included an emotional maturity scale based on the dimensions proposed by Singh and Bhargava (2005) and the Heartland Forgiveness Scale (HFS) developed by Thompson (2005). Data analysis was conducted using Pearson Product Moment correlation with the assistance of SPSS version 20. The results showed that most respondents were in the moderate category for both emotional maturity and forgiveness. The correlation test produced a significance value of 0.001 (< 0.05) with a correlation coefficient of 0.362 and a coefficient of determination of 13.1%. These findings indicate a significant positive relationship between emotional maturity and forgiveness; the higher the emotional maturity of adolescents, the higher their ability to forgive. This study emphasizes the importance of developing emotional maturity as a supporting factor in fostering forgiving attitudes among adolescents who experience romantic breakups. The implications of this research are expected to serve as a basis for intervention programs that support adolescent psychological well-being, as well as provide insights for teachers, parents, and related stakeholders in enhancing understanding of the role of emotional maturity in the forgiveness process.